2021
DOI: 10.3390/su13115794
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurs Traits/Characteristics and Innovation Performance of Waste Recycling Start-Ups in Ghana: An Application of the Upper Echelons Theory among SEED Award Winners

Abstract: Waste management has become a pressing environmental, social, and economic issue. In Ghana, the government has decentralized the waste management system to include private sector actors as key players to improve the collection, disposal, and recycling of waste. With this development, a heterogeneous population of entrepreneurs has engaged in waste recycling, achieving mixed results in terms of performance. The aim of this paper is to identify shared personality traits and characteristics of entrepreneurs that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 78 publications
0
4
0
Order By: Relevance
“…The results indicated that entrepreneur personality had a significant effect on innovation performance, hence, hypothesis 1 (H1) was accepted. This aligned with Cui & Song [27] and Dorcas et al [42] stating that higher self-confidence, strong creativity, and the willingness to take risks for business progress influenced innovation performance. Individuals who possess brilliant and distinct ideas from their competitors and have full confidence in their decisions can achieve superior innovation.…”
Section: Hypothesis Testing (Bootstrapping)supporting
confidence: 77%
“…The results indicated that entrepreneur personality had a significant effect on innovation performance, hence, hypothesis 1 (H1) was accepted. This aligned with Cui & Song [27] and Dorcas et al [42] stating that higher self-confidence, strong creativity, and the willingness to take risks for business progress influenced innovation performance. Individuals who possess brilliant and distinct ideas from their competitors and have full confidence in their decisions can achieve superior innovation.…”
Section: Hypothesis Testing (Bootstrapping)supporting
confidence: 77%
“…According to entrepreneurial literature, experience is more important than education in identifying opportunities (Light et al , 2017). Since then, there has been considerable debate about whether prior experience in a company setting affects entrepreneurs’ predicted success (Çakmak et al , 2018; Dorcas et al , 2021). Swart and Pretorius (2018) examined the likelihood of survival for newly created businesses, and they claim that increased human capital boosts an entrepreneur’s productivity, which results in increased earnings.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The demographics of CFOs are frequently employed as indicators of their managerial cognition and values (Sun et al, 2017). Age is a notable attribute that is an indication of a person’s experience and an internal motivator that influences behavioral decision-making (Dorcas et al, 2021). Older managers are more inclined to use conservative policies when making decisions (Hambrick & Mason, 1984).…”
Section: Literature Review and Hypothesismentioning
confidence: 99%